2022
DOI: 10.1007/s40615-022-01487-0
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Participant Diversity in Clinical Trials—Have We Made Progress for the Management of Obesity and Its Metabolic Sequelae in Diet, Drug, and Surgical Trials

Abstract: Objective Individuals from Black and Hispanic backgrounds represent a minority of the overall US population, yet are the populations most affected by the disease of obesity and its comorbid conditions. Black and Hispanic individuals remain underrepresented among participants in obesity clinical trials, despite the mandate by the National Institutes of Health (NIH) Revitalization Act of 1993. This systematic review evaluates the racial, ethnic, and gender diversity of clinical trials focused on ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Secondly, we included a diverse population in terms of socioeconomic status and ethnicity, including a significant proportion of Black African and Caribbean ethnicity individuals. This is important as clinical trial data includes primarily those of white ethnicity 48 . Third, our programme was entirely state‐funded via the NHS, which may have increased the uptake of liraglutide compared to other healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we included a diverse population in terms of socioeconomic status and ethnicity, including a significant proportion of Black African and Caribbean ethnicity individuals. This is important as clinical trial data includes primarily those of white ethnicity 48 . Third, our programme was entirely state‐funded via the NHS, which may have increased the uptake of liraglutide compared to other healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as clinical trial data includes primarily those of white ethnicity. 48 Third, our programme was entirely state-funded via the NHS, which may have increased the uptake of liraglutide compared to other healthcare systems. In fact, the median multiple deprivation index was 3, indicating our population was from relatively high levels of socioeconomic deprivation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The authors concluded that Black Americans and Hispanics who have a high prevalence of obesity were under‐represented, even in the trials that focused on obesity. Further, they state that the clinical study sites were often located in regions of the country where the prevalence of obesity is lower, and that the location of study sites in urban areas can add to this disparity, as populations in rural areas may benefit more from participation 25 …”
Section: Challenges For the Inclusion Of Participants Who Are Obese I...mentioning
confidence: 99%
“…Further, they state that the clinical study sites were often located in regions of the country where the prevalence of obesity is lower, and that the location of study sites in urban areas can add to this disparity, as populations in rural areas may benefit more from participation. 25…”
Section: Challenges For the Inclusion Of Participants Who Are Obese I...mentioning
confidence: 99%
“…While tirzepatide produces greater weight loss than semaglutide in patients with T2D [11], head-to-head trials evaluating these therapies in patients with overweight or obesity are not yet available. Further, it remains unclear whether the magnitude of weight loss observed in real-world settings mirrors that observed in RCTs, given well-described differences between these populations [12][13][14]. Finally, because these medications are costly and insurance coverage is limited for patients without T2D, real-world adherence may be reduced, attenuating the treatment effect in real-world settings.…”
Section: Introductionmentioning
confidence: 99%